Young surgeons entering the workforce in the City of Buenos Aires. Need for restructuring of the general surgery training system (Revista Argentina de Cirugía, 2021)
Background: Training in surgery has remained relatively uniform since the residency programs were introduced. The continuous advances in science have led to the progressive super-specialization of surgeons; 70% of them continue their training with a subspecialty.Objectives: The aim of this study was to identify the proportion of surgeons who dedicate hours of their practice in another activity and to analyze how surgeons enter the workforce.Material and methods: We conducted a prospective and descriptive cross-sectional study with data from a survey, records of the General Directorate of Teaching and Research, and records of competitive selection processes and professional profiles available online.Results: Of 435 survey respondents, 73.3% of the resident graduates continued postresidency training in a surgical subspecialty. Only 24.7% immediately started working in general surgery. Among the graduate trainees in general surgery, only 17.4% were exclusively dedicated to general surgery.Conclusions: The lack of confidence to perform procedures independently and the need for completing 4 years of training in the residency program in general surgery to start training in the professional field of interest, appear as the issued to be solved. We propose a 5-year program with a 2+3 model. The initial period comprises 24 months of basic training covering the general aspects of surgical practice.The second period of advanced training will provide thorough training in the subspecialty chosen. In the last year of the 5-year program trainees will have the opportunity to act as attending surgeons. General surgery, conceived as a subspecialty.
Keywords: residency; General Surgery; general surgeon; subspecialization; subspecialty; super specialization; workforce; fellowship; educational program